Low risk of cardiac complications in collegiate athletes after asymptomatic or mild COVID-19 infection - Klawitter, P.; Cowen, L.; Carhart, R. (Clinical Journal of Sport Medicine, 2022)
Objective: The objective of this study was to determine the utility of "standard" cardiac screening with EKG, echocardiography, and serum troponin T (hs-Tn T) testing after COVID infection in competitive college athletes.